Modernisasi Manajemen Pesantren Menyongsong Era Society 5.0 - AM Saifullah Aldeia; Nurul Qolbi Izazy; St Aflahah; Yuyun Libriyanti (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
Modernization of pesantren management is an important agenda item to be implemented immediately in welcoming the era of